2022
DOI: 10.3390/jcm11040903
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Screening Microvascular Complications in Type 2 Diabetic Patients Using Demographic, Clinical, and Laboratory Profiles

Abstract: Microvascular complications are one of the key causes of mortality among type 2 diabetic patients. This study was sought to investigate the use of a novel machine learning approach for predicting these complications using only the patient demographic, clinical, and laboratory profiles. A total of 96 Bangladeshi participants with type 2 diabetes were recruited during their routine hospital visits. All patient profiles were assessed by using a chi-squared (χ2) test to statistically determine the most important m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In patients with type 1 diabetes, atherosclerosis is associated with DR, and patients with DN have a greater coronary plaque burden than those with normoalbuminuria ( Kim et al, 2007 ; Lovshin et al, 2018 ). Next, cluster #5 was “machine learning.” It has been found that artificial intelligence (AI)-based machine learning can predict microvascular complications in diabetic patients ( Sambyal et al, 2021 ; Rashid et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 1 diabetes, atherosclerosis is associated with DR, and patients with DN have a greater coronary plaque burden than those with normoalbuminuria ( Kim et al, 2007 ; Lovshin et al, 2018 ). Next, cluster #5 was “machine learning.” It has been found that artificial intelligence (AI)-based machine learning can predict microvascular complications in diabetic patients ( Sambyal et al, 2021 ; Rashid et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significant observations show that the advanced structure with ML classifiers achieved an AUC ranging from 0.79 to 0.91. Rashid, M. et al [15] identified a root cause of death among T2-DM patients due to micro vascular problems. Their study aims to examine the use of the entire ML procedure in identifying issues using people's medical, clinical, and statistical examinations.…”
Section: Related Workmentioning
confidence: 99%
“…In this Special Issue, entitled “ Clinical Research on Type 2 Diabetes and Its Complications ” and published in the Journal of Clinical Medicine ( ), some valuable digital methodologies were used in different studies focusing on the type 2 diabetes syndrome. Novel machine learning techniques for predicting long-term complications are one of these approaches, as the studies of Huang, Rashid, and Shin et al depict [ 3 , 4 , 5 ]. The data presented by these authors suggest that machine learning may be more accurate in predicting diabetic microvascular complications than traditional methods.…”
mentioning
confidence: 99%